Analisis Pengaruh Layout Penyimpanan Bahan Baku terhadap First In First Out berdasarkan Hasil Jajak Pendapat Karyawan (Studi pada PT Indofood CBP Sukses Makmur TBK Divisi Packaging Purwakarta) - Fino Wahyudi Abdul; Muhammad Rizki Ramadhan (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
In a manufacturing company, the role of a warehouse for raw materials (storage) and warehouse for finished products (warehouse) is very important. Because it is impossible for the raw materials that have been ordered directly to be placed on the production floor. So it is with the finished product. It is also impossible for the resulting product to be distributed directly to consumers. This causes the need for a warehouse with a good layout. The aim of this research is to obtain the results of the analysis of the effect of the storage layout of raw materials on firsti in first out (FIFO). The data sources used are primary and secondary company data, as well as data obtained from the company. The theoretical basis used is the theory of influence, layout, and First In First Out. Based on the analysis of employee perception assessment data, it is concluded that the storage layout of raw materials has an effect on the FIFO system